Metal chloride‐graphite intercalation compounds for rechargeable metal‐ion batteries - Lu, Anbang; Wang, Fei; Liu, Zhendong; Wang, Yuchen; Gu, Yue; Wang, Shuang; Ye, Chong; Liu, Quanbing; Zhang, Chengzhi; Tan, Jun (Carbon energy, 2024)
The typical metal chloride‐graphite intercalation compounds (MC‐GICs) inherit intercalation capacity, high charge conductivity, and high tap density from graphite, and these are considered as one of the promising alternatives of graphite anode in rechargeable metal‐ion batteries (MIBs). Notably, the special interlayer decoupling effects and the introduction of extra conversion capacity by metal chloride could greatly break the capacity limitation of graphite anodes and achieve higher energy density in MIBs. The optimization of both graphite host and metal chloride species with specific structures endows MC‐GICs with design feasibility for different application requirements of different MIBs, such as several times the actual capacity compared to graphite anodes, rapid migration of large carriers, and other properties. Herein, a brief review has been provided with the latest understanding of conductivity characteristics and energy storage mechanisms of MC‐GICs and their interesting performance features of full potential application in rechargeable MIBs. Based on the existing research of MC‐GICs, necessary improvements and prospects in the near future have been put forward. Metal chloride‐graphite intercalation compounds are recognized as promising alternative electrode materials of graphite. It presents unique electronic characteristics and allows more metal‐ion storage with several energy storage mechanisms. Based on the designing of the graphite host, intercalator, and electrode structure, metal chloride‐graphite intercalation compounds delivered high capacity, fast electrochemical kinetics, and superior cycling stability for rechargeable metal‐ion batteries.